Success of Spontaneous Breathing Trials using Pressure Support Ventilation versus T-piece in Mechanically Ventilated Patients: A Randomised Clinical Trial - Monica Chhikara; Alka; Shilpa Popli; Amanpreet Hira; Manisha Yadav (Journal of Clinical and Diagnostic Research)
Introduction: The weaning process in mechanical ventilation is crucial, as it helps patient’s transition from dependence on the ventilator to breathing independently. The method used can impact patient outcomes, including the length of ventilation, complications and overall recovery. Proper weaning reduces the risk of complications such as ventilator-associated pneumonia and muscle weakness while promoting successful extubation and improved patient outcomes. Aim: To compare two methods of Spontaneous Breathing Trials (SBT): Pressure Support Ventilation (PSV) and T-piece trial for successful weaning in mechanically ventilated patients in critical care units. The secondary objective was to assess the attempts of SBT required for weaning in two groups of patients receiving T-piece and PSV. Materials and Methods: This prospective randomised clinical trial was conducted in the Department of Anaesthesia, Pt. BD Sharma Postgraduate Institute of Medical Sciences (PGIMS) (a tertiary care centre), Rohtak, Haryana, India after obtaining ethical approval. A total of 80 patients aged over 18 years who have been mechanically ventilated for a minimum of 24 hours but less than seven days in the Intensive Care Unit (ICU) were enrolled in the present study. After assessing readiness for weaning, patients were randomised to receive SBT via either PSV mode or T-piece and their ventilatory parameters were noted. Based on the success of the SBT, patients were classified into four groups according to the Weaning according to a New Definition (WIND) criteria. Data was analysed using Statistical Package for Social Sciences (SPSS) software version 22.0. Results: The mean age of patients in the pressure support group and the T-piece group was 42.75±18.271 years and 42.20±19.161 years, respectively. Demographic data, such as age, gender and parameters {Acute Physiology and Chronic Health Evaluation (APACHE) score, haemoglobin levels, blood sugar level, temperature, airway in-situ, duration of ventilation}, were comparable in both groups. The number of Separation Attempts (SA) required were significantly lower in the pressure support group, with a p-value of 0.001. The pressure support group had more successful weaning on day 1 compared to the T-piece group (p-value=0.001). Conclusion: The PSV is a better method of SBT for patients who have been mechanically ventilated in the ICU for more than 24 hours. The number of SBTs required for the PSV group was less than that required for the T-piece group.